2022
DOI: 10.1112/jlms.12674
|View full text |Cite
|
Sign up to set email alerts
|

Torus actions on manifolds with positive intermediate Ricci curvature

Abstract: We study closed, simply connected manifolds with positive 2 nd -intermediate Ricci curvature and large symmetry rank. In odd dimensions, we show that they are spheres. In even dimensions other than 6, we show that they must have positive Euler characteristic. Under stronger assumptions on the symmetry rank, we show that such even-dimensional manifolds must have trivial odd degree integral cohomology, and if the second Betti number is no more than 1, they are either spheres or complex projective spaces. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A natural starting point to consider symmetries in the presence of positive intermediate Ricci curvature is to consider those with Ric 2 > 0. Mouillé [18] in recent work has been able to extend the Maximal Symmetry Rank Theorem to closed, 𝑛-manifolds with Ric 2 > 0, showing that the symmetry rank of such manifolds is the same as for the positive curvature case, and moreover obtains a similar classification result.…”
Section: Large Symmetry and Discrete Symmetry Rankmentioning
confidence: 89%
See 1 more Smart Citation
“…A natural starting point to consider symmetries in the presence of positive intermediate Ricci curvature is to consider those with Ric 2 > 0. Mouillé [18] in recent work has been able to extend the Maximal Symmetry Rank Theorem to closed, 𝑛-manifolds with Ric 2 > 0, showing that the symmetry rank of such manifolds is the same as for the positive curvature case, and moreover obtains a similar classification result.…”
Section: Large Symmetry and Discrete Symmetry Rankmentioning
confidence: 89%
“…there are also metrics of positive Ric 𝑘 ′ with 𝑘 ′ < 𝑘 on such products. In particular, in Example 2.3 of Mouillé [18], he shows that one can put Ric 2 > 0 metrics on 𝑀 6 = 𝑆 3 × 𝑆 3 with 𝑇 3 symmetry, as well as Ric 2 > 0 on quotients by free torus actions of 𝑀 6 . These results are consistent with the almost maximal symmetry rank classification results mentioned earlier and suggest a connection between closed, simply-connected manifolds of nonnegative curvature with large symmetry rank and 𝑅𝑖𝑐 𝑘 > 0 for small 𝑘.…”
Section: Large Symmetry and Discrete Symmetry Rankmentioning
confidence: 99%
“…In particular, they have shown that Gromov's Betti number bound fails in the case of Ric [ d 2 ]+2 > 0 in any dimension d ≥ 5. Finally, we mention that the bound k ≤ d 2 also appears in several structural results of manifolds of Ric k > 0, see [GW,KM,Mo22,Xi97]. We refer to [Mo] for a collection of publications and preprints concerning the curvature conditions Ric k > 0.…”
Section: Corollary Bmentioning
confidence: 98%
“…Here, we follow the good description in [19]. For the forthcoming definitions, there is no widely used notation/terminology.…”
Section: Preliminariesmentioning
confidence: 99%